2022
DOI: 10.2196/35202
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Serious Games in Improving Memory Among Older Adults With Cognitive Impairment: Systematic Review and Meta-analysis

Abstract: Background Memory, one of the main cognitive functions, is known to decline with age. Serious games have been used for improving memory in older adults. The effectiveness of serious games in improving memory has been assessed by many studies. To draw definitive conclusions about the effectiveness of serious games, the findings of these studies need to be pooled and aggregated. Objective This study aimed to assess the effectiveness of serious games in im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Virtual reality (VR) technology and exergaming, especially, have been emerged as promising tools for studying and rehabilitating gait and balance impairments in people with PD, as it allows users to be engaged in an enriched and highly individualized complex environment [ 13 ]. In particular, exergaming is defined as technology-driven physical activities that requires participants to be active and/or exercise in order to play games, by using the full body motion as a principal mean of interaction [ 14 ]. Several studies have shown that interventions based on exergames promote the simultaneous training of cognitive and motor aspects and offer a number of stimuli and difficulty of the tasks adjusted to the patients’ needs, maintaining control and stimulus consistency [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality (VR) technology and exergaming, especially, have been emerged as promising tools for studying and rehabilitating gait and balance impairments in people with PD, as it allows users to be engaged in an enriched and highly individualized complex environment [ 13 ]. In particular, exergaming is defined as technology-driven physical activities that requires participants to be active and/or exercise in order to play games, by using the full body motion as a principal mean of interaction [ 14 ]. Several studies have shown that interventions based on exergames promote the simultaneous training of cognitive and motor aspects and offer a number of stimuli and difficulty of the tasks adjusted to the patients’ needs, maintaining control and stimulus consistency [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Technological advancements have overcome some of these barriers, serving to improve functioning, tracking, and mobility, and have the potential to not only alleviate caregiver burden but also enable individuals to successfully age in place [ 13 ]. Alternately, there exist multiple forms of computerized cognitive training programs, or serious games (named as such due to their primary purpose being other than pure entertainment), that have been shown to help improve verbal, nonverbal, and working memory and therefore potentially have a role in slowing or preventing cognitive decline [ 14 , 15 ]. Incorporating cognitive training strategies is another application of the metaverse for this population.…”
mentioning
confidence: 99%
“…Summarizing the features of the current AI-driven serious games is very important to explore how they have been developed and used and their current state to plan on how to leverage them in the current and future health care needs. Previous reviews did not focus on AI-driven serious games [36] and focused on a specific disease rather than health care in general [8][9][10][11][12][13]. Therefore, this review aimed to explore the features of AI-driven serious games in health care as reported by previous studies.…”
Section: Research Problem and Aimmentioning
confidence: 99%
“…In health care, serious games have been used for many purposes such as screening, diagnosing, education, prevention, and rehabilitation [ 4 , 5 ]. For example, serious games have shown promising results in improving health education [ 6 ]; acute pain management [ 7 ]; cognitive functions (eg, global cognition [ 8 ], memory [ 9 ], executive functions [ 10 ], and processing speed [ 11 ]); mental health disorders (eg, depression [ 12 ] and anxiety [ 13 ]); and functional, motor, and sensory functions [ 14 ]. Furthermore, serious games have the potential to diagnose and screen many diseases such as mild cognitive impairment [ 15 ], developmental dyslexia [ 16 ], and attention-deficit/hyperactivity disorder [ 17 ].…”
Section: Introductionmentioning
confidence: 99%